The Triumphs of Pelops and Bellerophon: Unique Mosaic Evidence of Romanitas in Late Roman Britain. (November 2022) - Beeson, Anthony; Nichol, Matt; Massey, Richard
Abstract: A Roman villa building at Mud Hole, Boxford, West Berkshire, was examined by excavation in 2017 and 2019, and found to be of probable fourth-century date. One room of this otherwise seemingly modest villa contained a remarkable late fourth-century figured mosaic, which features a number of rare mythological subjects not previously encountered in Britain. Inscriptions suggest the name of the villa owner (Caepio) and his wife (Fortunata), with a possible Spanish connection. The mosaic's central panel is ornamented with the triumphs of Pelops and Bellerophon, the former known only from two other mosaics, in Syria and Spain. The borders also contain depictions of stories unknown on other mosaics, but all concerned with aspects of triumph. The central panel is upheld by walking telamones (giants), otherwise only known on a mosaic from Tusculum, and the mosaicists have attempted to use foreshortening to give the floor a trompe l'oeil effect. The rare subjects depicted on the floor all relate to either Poseidon, Pelops, Bellerophon or Atlas, and suggest high standards of mythological knowledge and longevity of classical culture amongst the villa-owning inhabitants of late fourth-century Berkshire. The mosaic shows a connection to earlier depictions of the Pelops story, but is highly original in its interpretation of them and follows a contemporary trend, not previously encountered in Britain, of its subjects breaking out from their ornamental borders. The mosaic is an altogether exceptional discovery and can be considered an important example of late Roman art so far found in Britain.